2017
DOI: 10.5194/tc-2017-57
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring the snowpack depth with Unmanned Aerial System photogrammetry: comparison with manual probing and a 3D laser scanning over a sample plot

Abstract: Abstract.Photogrammetric surveys using Unmanned Aerial Systems (UAS) may represent an alternative to existing methods for measuring the distribution of snow, but additional efforts are still needed to establish this technique as a low-cost, yet precise tool. Importantly, existing works have mainly used sparse evaluation datasets that limit the insight into UAS performance at high spatial resolutions. Here, we compare a UAS-based photogrammetric map of snow depth with data acquired with a 5MultiStation and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 36 publications
(14 reference statements)
2
13
0
Order By: Relevance
“…Key point density decreased by almost 1 order of magnitude when comparing missions flown with snow more than 1 day old and missions with either deep fresh snow or smooth icy snowpacks. Previous studies have identified the drop in both elevation and SD accuracy due to deep fresh snow (Nolan et al 2015;Avanzi et al, 2017) and icy conditions (Gindraux et al, 2017). Here we demonstrate that D may be a useful indicator of such conditions and hence an indicator of the quality of SD estimates.…”
Section: Sfm Performance With Snowpack Condition Microtopography Andsupporting
confidence: 58%
See 4 more Smart Citations
“…Key point density decreased by almost 1 order of magnitude when comparing missions flown with snow more than 1 day old and missions with either deep fresh snow or smooth icy snowpacks. Previous studies have identified the drop in both elevation and SD accuracy due to deep fresh snow (Nolan et al 2015;Avanzi et al, 2017) and icy conditions (Gindraux et al, 2017). Here we demonstrate that D may be a useful indicator of such conditions and hence an indicator of the quality of SD estimates.…”
Section: Sfm Performance With Snowpack Condition Microtopography Andsupporting
confidence: 58%
“…1), with a tendency for underestimation in areas with substantial ground thatch layer. The underestimate in these conditions was approximately the same magnitude of the thatch height, leading us to hypothesize that they are related to an overestimate in the local DSM height as previously suggested (Nolan et al, 2015;Avanzi et al, 2017). This hypothesis could be tested in future studies using supplementary in situ elevation measurements (e.g.…”
Section: Geolocation and Sd Validationmentioning
confidence: 64%
See 3 more Smart Citations